2015
DOI: 10.1530/erc-14-0549
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cycle-dependent regulation of androgen receptor function

Abstract: The Androgen Receptor (AR) is a critical oncogene in prostate cancer (PCa) development and progression. Here we demonstrate cell cycle dependent regulation of AR activity, localization, and phosphorylation. We show that on three AR target genes, androgen-stimulated AR transactivation is highest in G1, decreased in S-phase, and abrogated in G2/M. This change in AR transactivation parallels changes in AR localization and phosphorylation. A combination of imaging techniques and quantitative analysis shows nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 48 publications
1
29
0
1
Order By: Relevance
“…However, the interphase activation of Aurora would be expected to be PC-1-independent. AR function is cell cycle-dependent, and S308 phosphorylation by Cdk1 regulates its localization and transcriptional activity (46). Additionally, phosphorylation of CHIP at Ser20 by Cdk5 promotes tAIF-mediated neuronal death (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, the interphase activation of Aurora would be expected to be PC-1-independent. AR function is cell cycle-dependent, and S308 phosphorylation by Cdk1 regulates its localization and transcriptional activity (46). Additionally, phosphorylation of CHIP at Ser20 by Cdk5 promotes tAIF-mediated neuronal death (30).…”
Section: Discussionmentioning
confidence: 99%
“…CDK1 activity promotes AR S81 phosphorylation and protein stabilization, thereby increasing AR activity (41). Recently, we reported that CDK1 phosphorylates AR on S308, and that this phosphorylation may regulate AR localization during mitosis (42). CDK1 activity increases as PCa progresses (29,43).…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle progression is driven by the rising and falling in levels of cyclins and cyclin dependent kinase (CDKs), in addition to the activation of these proteins 103 . In prostate cancer, AR is regulated in a cell-cycle-dependent manner 104 . Nuclear transactivation of AR is highest in G1 and decreases in S phase, while the same changes occur in AR phosphorylation and cellular localization 104 .…”
Section: Cell Cycle Regulation Prostate Cancermentioning
confidence: 99%
“…In prostate cancer, AR is regulated in a cell-cycle-dependent manner 104 . Nuclear transactivation of AR is highest in G1 and decreases in S phase, while the same changes occur in AR phosphorylation and cellular localization 104 . Further, CDK1 has been shown to phosphorylate AR on S308 in response to ligand binding 104 .…”
Section: Cell Cycle Regulation Prostate Cancermentioning
confidence: 99%